The effects of an adapted mental health literacy curriculum for secondary school students in Germany on mental health knowledge and help-seeking efficacy: results of a quasi-experimental pre-post evaluation study - Freţian, Alexandra Maria; Kirchhoff, Sandra; Bauer, Ullrich; Okan, Orkan (Frontiers in Public Health, 2023)
Background: Because the majority of mental illnesses develop early in life, effective preventative public mental health interventions are needed. Interventions fostering mental health literacy can be used to enhance personal resources and capacities to facilitate mental health care and thus, address help-seeking barriers. A Canadian mental health literacy school curriculum was adapted, piloted, and evaluated for the use in German schools. The study presents the intervention's effects on mental health knowledge and help-seeking efficacy among 10 th grade students in Germany.Methods: 10 th grade students (aged 14-17 years old) from one secondary school participated in a preand post-intervention control group study. Both groups completed a questionnaire at two time points assessing mental health knowledge and help-seeking efficacy. Repeated measure analysis of variance (ANOVA) was employed to evaluate the intervention's effects.Results: Data from 188 students was eligible for analysis. The analysis of the baseline data reveals a high comparability of the two groups in terms of demographics, and initial mental health knowledge and help-seeking efficacy scores. ANOVA results showed significant improvements for the intervention group having a large effect size for mental health knowledge (f = 0.574, p < 0.001, partial η 2 = .25) and a medium effect size for help-seeking efficacy (f = 0.311, p < 0.001, partial η 2 = .09).The first-time application and evaluation of an adapted mental health literacy school curriculum shows significant increases in mental health knowledge and help-seeking efficacy, two core dimensions of mental health literacy, among 10 th grade students in Germany. Further studies are needed to confirm these results as well as have a more in-depth analysis on the interrelations of the different dimensions of mental health knowledge and help-seeking practices.